2020
DOI: 10.5796/electrochemistry.20-64048
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Electrolyte Additives on Kinetic Parameters of Lithium-ion Transfer Reactions at Electrolyte/Graphite Interface

Abstract: The performance of the graphite anode of lithium-ion batteries is greatly affected by the solid electrolyte interphase (SEI) generated at the first charge. However, there are few studies on the kinetics of the lithium-ion intercalation/de-intercalation reaction in graphite to investigate the effect of SEI. In this study, the correlation between the interfacial lithium-ion transfer resistance (R ct ) and the double layer capacitance (C dl ) of graphite composite electrodes coated with various SEIs was investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…It was shown that the R ct at the f edge -defined HOPG was in the order of VC > EC > FEC. A similar trend was observed for graphite composite electrodes . Because the evaluated E a was the same for the three SEIs, the variation in the R ct was purely derived from the A .…”
Section: Frequency Factors: Quantifying Intercalation Sitessupporting
confidence: 71%
See 2 more Smart Citations
“…It was shown that the R ct at the f edge -defined HOPG was in the order of VC > EC > FEC. A similar trend was observed for graphite composite electrodes . Because the evaluated E a was the same for the three SEIs, the variation in the R ct was purely derived from the A .…”
Section: Frequency Factors: Quantifying Intercalation Sitessupporting
confidence: 71%
“…A similar trend was observed for graphite composite electrodes. 30 Because the evaluated E a was the same for the three SEIs, the variation in the R ct was purely derived from the A. Hence, the A was in the order of VC < EC < FEC.…”
Section: Frequency Factors: Quantifyingmentioning
confidence: 99%
See 1 more Smart Citation
“…219 He started his academic career as the assistant professor in 2017. As well as continuous studies on oxygen electrocatalysis, 220,221 his current research focuses on lithium-ion batteries 60,222,223 and other rechargeable batteries. One of the papers published in Electrochemistry has received Excellent Paper Award of ECSJ in 2021.…”
Section: Electrochemical Impedance Spectroscopymentioning
confidence: 99%
“…4,5 The SEI film suppresses the reductive decomposition of the electrolyte on the graphite surface after initial charging and prevents the exfoliation of the graphite surface by suppressing the cointercalation of lithium-ionsolvated compounds. 6 Various structures of SEI films have been reported, 5,7−10 influenced by the type of electrolytes, 11,12 electrolyte additives, 13,14 surface coating layers, 15,16 and charging−discharging conditions. 17,18 Graphite particles coated with an amorphous carbon layer are most commonly used in practical LIBs.…”
Section: Introductionmentioning
confidence: 99%